Pengembangan Multimedia Interaktif Pada Materi Gaya di Sekitar Kita untuk Siswa Kelas IV di SDS Islam Al-Furqon Pamekasan - Reskiya Ramadani; Ika Dian Rahmawati (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This study was motivated by the low level of students' interest and attention during the learning process, which was attributed to the use of learning media that were insufficiently engaging, lacked interactivity, and supported predominantly teacher-centered instruction, causing students to become easily bored and less actively involved in classroom learning. Therefore, this study employed a Research and Development (R&D) approach to develop interactive multimedia on the topic of Forces in Our Surroundings for fourth-grade students at SDS Islam Al-Furqon Pamekasan. The development process adopted the 4D model, consisting of the Define, Design, Develop, and Disseminate stages. The resulting product was an interactive multimedia application integrating learning materials, visualizations, and formative assessments to support the learning process. The feasibility of the product was determined through expert validation. The validation results indicated that the interactive multimedia achieved valid to highly valid categories, with scores of 92% from the instructional design expert, 83% from the material expert, 78% from the language expert, and 96% from the media expert. The effectiveness of the multimedia was demonstrated through teacher and student activities during the learning process. In the limited trial, teacher activity reached 96.15% and student activity reached 88.70%, while in the implementation trial, teacher activity remained at 96.15% and student activity increased to 94.40%. In addition, student learning outcomes showed a 100% mastery rate. The attractiveness of the multimedia also received highly positive responses. Student response questionnaire results reached 88.93% in the limited trial and increased to 97.49% in the implementation trial. These findings indicate that the developed interactive multimedia is feasible, effective, and attractive for use in teaching the topic of Forces in Our Surroundings in elementary schools.